Towards modelling of the environmental fate of pharmaceuticals using the QSPR-MM scheme. (October 2015) - Jagiello, Karolina; Mostrag-Szlichtyng, Aleksandra; Gajewicz, Agnieszka; Kawai, Toru; Imaizumi, Yoshitaka; Sakurai, Takeo; Yamamoto, Hiroshi; Tatarazako, Norihisa; Mizukawa, Kaoruko; Aoki, Yasunobu; Suzuki, Noriyuki; Watanabe, Haruna; et al.
Abstract: Pharmaceuticals are considered as a new, important group of pollutants. These compounds can enter the environment via several routes and can disturb the natural balance of ecosystems. Factors affecting the environmental fate of medical substances can be determined with computational modelling. The routine application of the modelling methodology in the environmental risk assessment for newly designed pharmaceuticals would enable prediction of their important physical/chemical properties and forecasting their long-range transport and fate. In this contribution, we present the existing state-of-the-art and review the currently available modelling tools of two groups: Quantitative Structure-Property Relationship techniques and Multimedia Mass-balance models. We discuss the current research needs in the context of extending the applicability of the existing tools onto pharmaceuticals, being a more structurally diversified group of contaminants than persistence organic pollutants, for which the majority of the existing models have been originally developed. Highlights: Multimedia fate models applied for pharmaceuticals are reviewed. QSPR approach to predict physical/chemical properties of pharmaceuticals is reviewed. QSPR-MM combined model is suggested to predict Pov and LRTP of chemical pollutants.